2006
DOI: 10.1038/sj.bmt.1705263
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous alemtuzumab vs ATG in adjusted conditioning for allogeneic transplantation: influence of Campath dose on lymphoid recovery, mixed chimerism and survival

Abstract: Sixty-nine consecutive patients (median age 54 years) were prospectively enrolled in a single-institution protocol for allogeneic transplantation with adjusted non-myeloablative fludarabine-melfalan-based conditioning including cyclosporin A and MMF, and one of three modes of serotherapy. Thirty-one donors (45%) were unrelated. The first cohort of 29 had ATG (Thymoglobulin 2 mg/kg  3 days), the subsequent 26 had Campath 30 mg  3 days subcutaneously, and the final cohort of 14 had 30 mg Campath once. The grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 35 publications
3
40
0
Order By: Relevance
“…In order to prevent these complications, several groups have successfully reduced the alemtuzumab dose as part of the conditioning regimen for sibling and UD transplantation (total dose of 10-50 mg). [22][23][24][25] The schedule of pretransplant alemtuzumab, in addition to dose, will also have an effect on its biodistribution and clearance. 26 The earlier in the conditioning regimen that alemtuzumab is given, the less active drug that will be available post transplant.…”
Section: Discussionmentioning
confidence: 99%
“…In order to prevent these complications, several groups have successfully reduced the alemtuzumab dose as part of the conditioning regimen for sibling and UD transplantation (total dose of 10-50 mg). [22][23][24][25] The schedule of pretransplant alemtuzumab, in addition to dose, will also have an effect on its biodistribution and clearance. 26 The earlier in the conditioning regimen that alemtuzumab is given, the less active drug that will be available post transplant.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we intend to replace alemtuzumab with a reduced dose of rabbit ATG (Fresenius) resulting in a possibly milder immunosuppression post transplant. 25 Furthermore, we plan to prospectively study an intensified-conditioning regimen for patients up to 65 years old with addition of treosulfan, taking into account the aforementioned negative impact of age and, possibly, RIC 6 on outcome, as well as the active disease most of our patients have at the time of second allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has compared alemtuzumab with other agents for in vivo T-cell depletion. Juliusson et al (2006) found that patients who received alemtuzumab as part of the conditioning regimen initially had less initial toxicity with fewer fevers and lower transfusion requirements, the patients who received 30 mg/day for three consecutive days were more likely to have mixed chimerism post-transplant requiring DLI, and had more serious opportunistic infections which translated to greater non-relapse mortality. At the present time, the role of alemtuzumab in non-myeloablative stem cell transplant for CLL is uncertain.…”
Section: Alemtuzumab In Autologous Stem Cell Transplantationmentioning
confidence: 99%